RETRACTED: Altitude controller influence on environmental and economic performance of NGV fuel-powered engines - Simonyan Arman; Mosikyan Karapet; Balayan Razmik; Shaghoyan Viktorya (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001